The Contest Problem Book I : Annual High School Mathematics Examinations 1950-1960 - Salkind, Charles T. (Anneli Lax new mathematical library., 2012)
The annual high school contests have been sponsored since 1950 by the Mathematical Association of America and the Society of Actuaries, and more recently by Mu Alpha Theta (1965), the National Council of Teachers of Mathematics (1967) and the Casulty Actuarial Society (1971). Problems from the contests during the periods 1950-1960 are published in Volume 5 of the New Mathematical Library, and those for 1966-1972 are published in Volume 25. This volume contains those for the period 1961-1965. The questions were compiled by C.T. Salkind, Chairman of the Committee on High School Contests during the period, who also prepared the solutions for the contest problems. Professor Salkind died in 1968. In preparing this and the other Contest Problem Books, the editors of the NML have expanded these solutions with added alternative solutions.